PENGARUH AKTIVITAS KOMITE AUDIT DAN MULTIPLE LARGE OWNERSHIP STRUCTURE TERHADAP BIAYA AUDIT - Muhamad Rifqi Muharam; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of audit committee activities and multiple large ownership structures as independent variables on audit fees as the dependent variable. This study refers to Adelopo's research (2007) in England with some modifications to the control variables and the number of research sample populations.The population in this study are all non-financial companies in Indonesia listed on the Indonesia Stock Exchange in 2019. The method used is purposive sampling. Samples that meet the requirements for the study amounted to 127 companies. Testing the sample using multiple regression analysis to test both hypotheses in the study.Of the two research hypotheses, the results of the first study show that the activities of the audit committee do not have a significant effect on audit fees. Meanwhile, in the second hypothesis, the multiple large ownership structure does not have a significant effect on audit fees. This is due to the number of owners of block shares of companies in Indonesia tending to be less than four, so it is classified as a dispersed share ownership structure.